A new role for AMP‐activated protein kinase in the circadian regulation of L‐type voltage‐gated calcium channels in late‐stage embryonic retinal photoreceptors. (22nd September 2015) - Huang, Cathy C.Y.; Shi, Liheng; Lin, Chia‐Hung; Kim, Andy Jeesu; Ko, Michael L.; Ko, Gladys Y.‐P.
Abstract: AMP‐activated protein kinase (AMPK) is a cellular energy sensor, which is activated when the intracellular ATP production decreases. The activities of AMPK display circadian rhythms in various organs and tissues, indicating that AMPK is involved in the circadian regulation of cellular metabolism. In vertebrate retina, the circadian clocks regulate many aspects of retinal function and physiology, including light/dark adaption, but whether and how AMPK was involved in the retinal circadian rhythm was not known. We hypothesized that the activation of AMPK (measured as phosphorylated AMPK) in the retina was under circadian control, and AMPK might interact with other intracellular signaling molecules to regulate photoreceptor physiology. We combined ATP assays, western blots, immunostaining, patch‐clamp recordings, and pharmacological treatments to decipher the role of AMPK in the circadian regulation of photoreceptor physiology. We found that the overall retinal ATP content displayed a diurnal rhythm that peaked at early night, which was nearly anti‐phase to the diurnal and circadian rhythms of AMPK phosphorylation. AMPK was also involved in the circadian phase‐dependent regulation of photoreceptor L‐type voltage‐gated calcium channels (L‐VGCCs), the ion channel essential for sustained neurotransmitter release. The activation of AMPK dampened the L‐VGCC currents at night with a corresponding decrease in protein expression of the L‐VGCCα1 pore‐forming subunit, while inhibition of AMPK increased the L‐VGCC current during the day. AMPK appeared to be upstream of extracellular‐signal‐regulated kinase and mammalian/mechanistic target of rapamycin complex 1 (mTORC1) but downstream of adenylyl cyclase in regulating the circadian rhythm of L‐VGCCs. Hence, as a cellular energy sensor, AMPK integrates into the cell signaling network to regulate the circadian rhythm of photoreceptor physiology. We found that in chicken embryonic retina, the activation of AMP‐activated protein kinase (AMPK) is under circadian control and anti‐phase to the retinal ATP rhythm. While ATP content is higher at night, phosphorylated AMPK (pAMPK) is higher during the day. AMPK appears to be upstream of extracellular signal‐regulated kinase (ERK), protein kinase B (AKT), and mammalian target of rapamycin complex 1 (mTORC1) but downstream of adenylyl cyclase in regulating the circadian rhythm of L‐VGCCs. Therefore, as a cellular energy sensor, AMPK integrates into the cell signaling network to regulate the circadian rhythm of photoreceptor physiology. Abstract : We found that in chicken embryonic retina, the activation of AMP‐activated protein kinase (AMPK) is under circadian control and anti‐phase to the retinal ATP rhythm. While ATP content is higher at night, phosphorylated AMPK (pAMPK) is higher during the day. AMPK appears to be upstream of extracellular signal‐regulated kinase (ERK), protein kinase B (AKT), and mammalian target of rapamycin complex 1 (mTORC1) but downstream of adenylyl cyclase in regulating the circadian rhythm of L‐VGCCs. Therefore, as a cellular energy sensor, AMPK integrates into the cell signaling network to regulate the circadian rhythm of photoreceptor physiology.